DEVELOPMENT OF A PREDICTION MODEL FOR THE BEHAVIOR OF BOLTED STRUCTURE WITH AN ELASTIC PART JOINT BASED ON METAMODEL APPROACH - Haiek, Mohammed; Lakhal, Yassine; Ben Said Amrani, Nabil; El Ansari, Youness; Sarsri, Driss (Journal of Applied Engineering Science, 2023)
This paper aims to establish a metamodel for predicting the mechanical behavior of bolted structures with elastic parts, regardless the changes in input parameters from a set of simulation data. First, we collect information from a parametric analysis based on numerical finite element simulation tests. Then, the metamodel is built using the radial spline basis function method. Following that, an iterative fitting process based on the metamodel-simulation coupling is used to improve the model’s fidelity. Finally, the metamodel is validated by comparing and analysing the error rate between the metamodel and the simulation in order to reduce the computation time towards 2 seconds.
Keywords: bolted mechanical structure, metamodel, dynamic analysis, radial basis function method (RBF), stress von mises and strain